Edukasi Kesehatan Makanan Sehat Bagi Anak di SD Negeri 1 Gumuk Banyuwangi - Hariani, Wahyu Fuji; Indah Kurniawati (Jurnal Pengabdian Masyarakat (JUDIMAS), 2025)
Nutritious food provides a variety of essential nutrients that the body requires. Snacking is a popular eating habit among children, enjoyed for its convenience and tasty appeal, especially those in elementary school. Unhealthy food can have negative impacts on children's health. Selecting snacks at random can result in decreased appetite and nutritional issues in kids, resulting in underweight and obesity. This activity aimed to educate children about healthy foods in school so that they can choose healthy and unhealthy snacks and improve students' knowledge and attitudes towards healthy foods to be consumed at school. The method used was counseling on recognizing healthy and unhealthy foods. Conclusion: The assessment of students’ knowledge and attitudes at SDN 1 Gumuk reveals a notable improvement in their understanding and awareness of distinguishing between healthy and unhealthy food options, as well as identifying suitable colors of healthy foods for consumption